Prediction of airway deformation effect on pulmonary air-particle dynamics: A numerical study - Zhao, Jianan; Feng, Yu; Koshiyama, Kenichiro; Wu, Huimin (Physics of Fluids, 2021)
Most existing whole lung models neglect the airway deformation kinematics and assume the lung airways are static. However, neglecting the airway deformation effect on pulmonary air-particle flow dynamics significantly limits the modeling capability under disease-specific lung conditions. Therefore, a novel elastic truncated whole-lung (TWL) modeling framework has been developed to simulate the disease-specific airway deformation kinematics simultaneously with pulmonary air-particle flow dynamics using one-way coupled Euler–Lagrange method plus the dynamic mesh method. Specifically, the deformation kinematics of the elastic TWL model was calibrated with clinical data and pulmonary function test results for both healthy lung and lungs with chronic obstructive pulmonary diseases (COPDs). The transport dynamics of spherical sub micrometer and micrometer particles were investigated. Results show that noticeable differences in air-particle flow predictions between static and elastic lung models can be found, which demonstrates the necessity to model airway deformation kinematics in whole-lung models. The elastic TWL model predicted lower deposition fraction in mouth-throat regions and higher deposition fraction in lower airways. The effect of disease-specific airway deformation kinematics on particle transport and deposition in the whole lung was investigated, with a focus on the targeted drug delivery efficiency in small airways from generation (G8) to alveoli as the designated lung sites for COPD treatment using inhalation therapy. Simulation results indicate that with the exacerbation of COPD disease conditions, the highest delivery efficiency of the inhaled drug particles decreases which indicates that delivering aerosolized medications to small airways to treat COPD is more challenging for patients with severe disease conditions.